The Influence of Government Responsibility and Community Participation in the Implementation of Village Sustainable Development Goals - Ardi Wiranata Moogangga; Niswatin Niswatin; Nilawaty Yusuf (International Forum of Researchers and Lecturers, 2025)
This research aims to determine the influence of government responsibility and community participation in the implementation of sustainable development goals in the village of Torosiaje both partially and simultaneously. This study employs a quantitative method. The data source used in this research is primary data obtained from questionnaires distributed to the government and the community of Torosiaje village. The data analysis technique in this study is descriptive quantitative analysis using t-statistical tests and the coefficient of determination test (Adjusted R Square) using IBM SPSS 25 for Windows. The research results indicate that 1. Government responsibility has a positive and significant effect on the implementation of the Village Sustainable Development Goals. 2. Community participation has a positive and significant effect on the implementation of the Village Sustainable Development Goals. 3. Based on the results of simple linear regression analysis, the coefficient of determination (R²) value for government responsibility is 42.2%, which means that 42.2% of the variation in the implementation of the Village Sustainable Development Goals in Torosiaje Village can be explained by government responsibility, while the remaining 57.8% is influenced by other factors outside the research model. For community participation, the R² value is 39.6%, indicating that 39.6% of the variation in the implementation of the Village Sustainable Development Goals can be explained by community participation, while the remaining 60.4% is explained by other factors outside the research model.